Impact of Seeds of Andizhan-36 Cotton Light And Various Methods for Cotton Harvesting - Atabaeva Mamura Sadirdin Kizi; Qodirov Odiljon; Xoliqova Gulirano (Academia Open, 2019)
With the use of resource-saving agricultural technology, using a new combine unit, once in the fall, nitrogen was applied at 50% of the annual rate of nitrogen 200% in liquid ammonia and the remaining 50% in the form of cotton ammonium nitrate. In the series and double-planted variants, the planting thickness of the cotton was greater than 1.2-5.9 thousand tons per hectare compared to the other variants of the system. 0.4 c / ha, yielding an additional yield of 4.1-5.9 c / ha compared to the control options and achieving maximum economic efficiency. Net profit from this option is 2079,1-2793.7 thousand sum, profitability rate is 52.3-68.4%, net profit per control option is 1127,7-1569,3 thousand sum, profitability rate is 29,1% up to 38.8%.